Film and television in education: A aesthetic approach to the moving image - Watson, Robert (The Falmer Press Library on aesthetic education, 1990)
Until recently film has been impractical and expensive to teach, but television and video have provided unprecedented opportunities. Not only is it becoming possible for everyone to make use of a library of films on video, subjecting them to close evaluative study, but also, with the increasing availability of video cameras in schools and colleges, it is becoming possible for everyone to learn the language of this richly expressive form by using it. Through an engaged analysis of the beginnings of film, the nature of expression, the conventions of film and television, the development of narrative, and modern film theories, Robert Watson provides an aesthetic framework for film study which has implications and numerous suggestions for practical creative work.